Impermanence of somatic embryogenesis: the effects of and solutions to gradual aging of peach palm (Bactris gasipaes Kunth) cultures in vitro - Ree, Joseph Francis (2019)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Ciências Agrárias, Programa de Pós-Graduação em Recursos Genéticos Vegetais, Florianópolis, 2019.